2016
DOI: 10.1055/s-0042-112127
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and its Implications in Oxidative Stress Influencing the Pathogenesis of Osteoporosis in Adults with Down Syndrome: A Cohort Study

Abstract: People with Down syndrome (DS) show lower bone mass density (BMD) and a higher prevalence of hypothyroidism compared to general population. Furthermore, DS is a well-known high oxidative stress (OS) condition because genes involved in OS map on chromosome 21. Thyroid function too is involved in OS. Since both thyroid function and OS lead to lower BMD and osteoporotic fractures, we have explored correlations among BMD, thyroid hormones, and parameters of OS in DS adults. A total of 105 DS patients (48 males; 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In the general population subclinical hypothyroidism is considered a risk factor for progression to overt hypothyroidism, Hashimoto's disease, hyperlipidemia, osteoporosis, and mood disturbance; and subclinical hyperthyroidism increases risk for progression to overt hyperthyroidism, thyroid nodules, Grave's disease, atrial fibrillation, osteoporosis, and mood/anxiety disorders. The relationship between thyroid disease and other medical conditions is beginning to be explored in children and adults with DS, with a recent study suggesting a role for both hypothyroidism and oxidative stress in association with osteoporosis (Villani et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population subclinical hypothyroidism is considered a risk factor for progression to overt hypothyroidism, Hashimoto's disease, hyperlipidemia, osteoporosis, and mood disturbance; and subclinical hyperthyroidism increases risk for progression to overt hyperthyroidism, thyroid nodules, Grave's disease, atrial fibrillation, osteoporosis, and mood/anxiety disorders. The relationship between thyroid disease and other medical conditions is beginning to be explored in children and adults with DS, with a recent study suggesting a role for both hypothyroidism and oxidative stress in association with osteoporosis (Villani et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus medications which inhibit bone resorption may not be an effective treatment. Research studies addressing bone formation and turnover, hypogonadism, and other endocrine disorders such as low thyroid or parathyroid hormone, oxidative stress, and effects on bone mass are indicated (Fowler et al, ; Villani et al, ; Zubillaga et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, DS is also characterized by high levels of chronic inflammation markers (Sullivan et al, 2017) and this condition too was shown to play a role in the prognosis of CoVID‐19 (Tay, Poh, Rénia, MacAry, & Ng, 2020). In addition, individuals with DS experience early aging of multiple organs and systems, leading to the development of a wide spectrum of comorbidities, including endocrinopathies, neurological, rheumatic, musculoskeletal diseases (Carfì et al, 2020), and high oxidative stress (Villani et al, 2016). Several anatomic abnormalities of the upper airways, muscular hypotonia, and obesity increase the likelihood of proximal airway obstruction, dysphagia, and obstructive sleep apnea (OSA) in individuals with DS, which is a predisposing factor for pulmonary hypertension, another risk factor for more severe CoVID‐19 infection (Bush et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Increased ageing and early onset of ageing related decline add further burden [22] [23] [24]. Thyroid dysfunction is commonly identified among people with DS, with hypothyroidism the most common presentation [25] [26] impacting significantly on skeletal health and later life osteoporosis [27] [28]. As people with DS age the prevalence of Alzheimer 1235 Health dementia and associated epilepsy increases [29].…”
Section: Down Syndrome and Osteoporosismentioning
confidence: 99%